An active dry electrode ecg interface circuit for wearable sensors. (November 2017) - Yang, Yintang; Yang, Zheng; Zhu, Zhangming; Wang, Jingmin
Abstract: A high performance active dry electrode interface circuit for ECG signal monitoring in 0.18 µm CMOS process is presented in this paper. AC-coupled core amplifier, input impedance boost loop and CMFB (Common-mode Feedback) circuit are applied in this analog front-end circuit. The programmable gain of the core amplifier is set from 12 dB to 40 dB. With the input impedance boost loop, a constant 2.4 GΩ input impedance is achieved (0.1–150 Hz @ typical condition). CMFB circuit is utilized to reduce common-mode interference, and the CMRR reaches 85 dB with the configuration of ac gain 40 dB. In this design, amplifier-based active dry electrode is utilized, which achieves better noise performance than buffer-based active electrode.